Blind OFDM channel estimation through simple linear precoding. - Petropulu, A.
A novel approach of blind channel estimation for orthogonal frequency-division multiplexing (OFDM) systems is proposed. A linear transformation is applied on each block before it enters the OFDM system. The transform imposes a correlation structure on the transmitted blocks, which is exploited at the receiver to recover the channel via simple cross-correlation operations. The proposed approach is computationally simple and converges fast, which makes it a good candidate for estimation of fast-varying channels. Its performance is tested analytically, through a mean-square error analysis, and also via simulations. Results show that it compares favorably to the training-based scheme used in the IEEE 802.11a wireless standard.
Keywords: IEEE 802.11a wireless standard; OFDM; Channel estimation; Cross correlation operations; Fast varying channels; Linear precoding; Linear transformation; Mean square error analysis; Orthogonal frequency division multiplexing system